A comprehensive review of natural products in rheumatoid arthritis: therapeutic potential and mechanisms - Han, Yuli; Chen, Shujing; Liu, Changqing; Sun, Huihui; Jia, Zhaoyu; Shi, Jiaxin; Li, Jin; Chang, Yanxu (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a classic autoimmune disease caused by a combination of genetic and environmental factors. The multiple and comprehensive pathologies involving the whole body’s immune system and local organs and tissues make it challenging to control or cure them clinically. Fortunately, there are increasing reports that multiple non-toxic or low-toxicity natural products and their derivatives (NP&TDs) have positive therapeutic effects on RA. This review focuses on the potential mechanisms of NP&TDs against RA and aims to provide constructive information for developing rational clinical therapies. Active components of NP&TDs can play therapeutic and palliative roles in RA through multiple biological mechanisms. These mechanisms primarily involve immunosuppressive, anti-inflammatory, autophagic, and apoptotic pathways. Multiple targets- and receptor-coupled signal transduction can directly or indirectly modulates the nuclear transcription factors NF-κB, NFATc1, STAT3, and HIF-1α, which in turn regulate the production of several downstream pro-inflammatory cytokines, chemokines, immunocytes maturation and differentiation, immune complexes, proliferation, and apoptosis regulatory genes. Among these NP&TDs, the tripterygium-type ingredients, the artemisinin-type ingredients, and the paeony-type ingredients have been reported to be the mainstay in treating RA. Mechanistically, immunosuppression and anti-inflammation are still the primary therapeutic mechanisms. Nevertheless, the direct binding targets and pharmacodynamic mechanisms require further in-depth studies.